EUGENE: an optimisation model for integrated regional solid waste management planning. (1st January 1999) - Berger, C.; Savard, G.; Wizere, A.
This paper presents a sophisticated mixed-integer linear programming model developed to help regional decision-makers in the long-term planning of solid waste management activities. The model removes practically all the limitations of earlier integrated waste management models. All the features and capabilities of the tool are described in technical and non-technical language. The paper includes statistics from a real-world application, and some directions for future developments.